Water Splitting on Aluminum Porphyrins To Form Hydrogen and Hydrogen Peroxide by One Photon of Visible Light - Kuttassery, Fazalurahman; Sagawa, Shogo; Mathew, Siby; Nabetani, Yu; Iwase, Akihide; Kudo, Akihiko; Tachibana, Hiroshi; Inoue, Haruo (ACS applied energy materials, 2019)
Artificial photosynthesis, which splits water into H2/O2 or reduces CO2 and N2 by visible light, catalyzed by molecular catalysts (MCs) with/without being coupled with a solar cell should serve as one of the most promising renewable energy systems. There still, however, exist bottleneck subjects to be resolved in the MCs’ approach, despite the recent progress. The key subject is the “photon-flux-density problem” of the rarefied sunlight radiation, which leads to a difficulty for the stepwise four-photon excitation of MCs to induce oxygen evolution from water. On the basis of our recent challenges on the two-electron oxidation of water by one-photon visible light excitation of an MC, where the MC does not need to wait for the next photon’s arrival, here we report an artificial photosynthesis system that produces H2 and H2O2 simultaneously on highly earth-abundant element-based aluminum-porphyrins by only one-photon excitation of visible light as the first exemplum to overcome the bottleneck.